Optimizing a vaseline–lanolin ointment base for Momordica charantia extract using a simplex lattice design - Muh Fajar Fauzi; Sarmoko; Tantri Liris Nareswari; Ahmad Bayu Satriawan; Nisa Yulianti Suprahman; Evi Kurniawaty (Pharmacy Reports, 2026)
Topical delivery of Momordica charantia (bitter melon) extract is a promising approach for anti-inflammatory and antioxidant therapy, yet the performance of the dosage form depends strongly on the composition of the formulation base. This study aimed to optimize a two-component vaseline–lanolin ointment base for M. charantia extract using a simplex lattice mixture design. Five blends spanning the binary mixture space were prepared and characterized for viscosity, spreadability, adhesiveness, and pH. Polynomial mixture models were fitted to each response, model adequacy was assessed by analysis of variance and lack-of-fit testing, and a multi-response Derringer desirability function was applied to locate a compromise optimum, which was then verified experimentally. Increasing the lanolin proportion generally increased viscosity and adhesiveness but reduced spreadability, whereas higher vaseline fractions improved spreadability while maintaining pH within a skin-compatible range. The models showed good fit and predictive utility, and the selected blend (vaseline:lanolin = 70:30) met all predefined physical criteria, with observed responses showing no significant difference from predicted values. In conclusion, simplex lattice optimization efficiently guided the vaseline–lanolin ratio toward a base with favorable rheological properties, providing a useful and reproducible platform for incorporating M. charantia extract in future efficacy and stability studies.